Does Social Protection Affect Infant Welfare? - Handoyo, Felix Wisnu (Jurnal Ekonomi Kesehatan Indonesia, 2020)
This research aims to assess the impact of conditional cash transfer (PKH) program on infant welfare. The poor people usually treated their babies inadequately due to of lack of resources. Government intervention by social protection program is expected to contribute to increase infant welfare. Infant welfare determines their quality of future life, and to some extent will determine the quality of human resources in a country. This research uses two micro data set which are Indonesia family life survey (IFLS) 4 and 5. The method is using econometrics with difference-in-differences (DiD) model to measure impact of the CCT program. Then, this research reveals that CCT (PKH) program is significantly positive affected to infant health status by 1.02% with OLS (2.39% using odered-probit and 4.38% using ordered-logit). However, the CCT program is insignificantly affected to increase infant weight. As a result, CCT program has just contributed to increase the infant welfare by increasing health status. By the result, the program should need to be improved and extended for beneficiaries in the future. By improving and extending program, the infant welfare will increase by health status indicator By this research, we can see how the significance of the program is contributed to the quality of Indonesia’s human resources by improving infant health status.